Contrast Induced Nephropathy and Gender Variation - Siddique, Md Abu; Subedi, Bikash; Arzu, Jahanara; Ahmed, Quazi Arif; Awal, Anisul; Sarker, Dilip Kumar; Islam, Md Sirajul; Rahman, Md Mukhlesur; Ahmed, Md Khursed; Fatema, Nilufar; Sultan, Md Ashraf Uddin; Zaman, SM Mustafa; et al. (University Heart Journal, 2011)
Contrast-induced nephropathy (CIN) is a recognized complication after percutaneous interventions (PCI). We sought to determine the impact of gender on incidence of CIN. Of a total 200 patients who underwent PCI, there were 33 (16.5%) who developed CIN (defined as > 25% rise in creatinine after PCI). CIN was present in 23.6% of female versus 17.4% of male patients (p < 0.0001). Multivariate analysis showed that female gender (p < 0.0001), pre-PCI chronic renal failure (CRF) (OR= 1.8, 95% CI = 1.53a€"2.10, p < 0.0001), diabetes mellitus (OR = 1.5, 95%, p < 0.0001), age (OR = 1.01, p < 0.0001), and hypertension (OR = 1.2, p = 0.0035) were independent predictors of CIN. By multivariate analysis only baseline CRF, diabetes, age, functional NYHA IV class were identified as independent risk factor for CIN. Female gender is an independent predictor of CIN development. Key words: Contrast-induced nephropathy; Percutaneous interventions; Serum Creatinine. DOI: 10.3329/uhj.v6i1.7184 University Heart Journal Vol.6(1) 2010 pp.18-20